How does trade affect regional inequalities? - Andres Rodriguez-Pose; Nicholas Gill (European Regional Science Association (ERSA), 2004)
As part of the ongoing globalisation of the world economy, the past twenty-five years have witnessed a steep rise in the amount of trade between nations, as well as changes in the composition of trade. This has been linked to economic growth, with most literature on the subject highlighting the benefits of greater openness. Concurrently, however, regional spatial inequalities within nations have also tended to increase steadily. In this paper we explore to what extent there is a link between the phenomena of increased trade flows and regional inequalities. We present a preliminary empirical evaluation based on eight major world economies, and ground these results in the theoretical literature. It emerges that the link between trade and regional inequalities is evidenced most strongly when sectoral shifts in the composition of trade are accounted for. Specifically, we find that as trade in primary sector goods loses importance in the composition of total trade, regional inequalities are likely to increase. Such an impact of changes in the composition of trade on regional inequalities is likely to have a greater negative impact on developing than on developed countries for two reasons. First, because the dimension of intra-national disparities tends to be greater in the developing than in the developed world. Second, because the share of agricultural trade in developing countries has traditionally been higher and has been declining at a much faster rate in recent decades.
Keywords: 330